TEACHING VOCABULARY BY USING RIDDLE GAME - Safitri, Ellyani; Sutapa Y, Y Gatot; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aims of this research was to find the empirical evidence of riddle game in teaching English vocabulary to the seventh grade students of SMP Negeri 7 Sungai Raya in Academic Year 2018/2019.. This study employed Pre-Experimental with one group pre-test and post-test design. The writer took the sample by using cluster random sampling to determine the participant of reseach consisted of 30 students. The data were collected by measurement technique and the tool of data collection was multiple choice test. Referring to the research findings, it was showed that the technique was effective in increasing the studentsâ€™ vocabulary achievement with t-test calculation resulted which was higher the t-critical and the effect size was 1.97 categorized as strong effect. To conclude,the use of riddle game for teaching vocabulary has a very strong effect in increase studentsâ€™ vocabulary achievement due to the learning process where the students played with each other, interacted and as a result they cooperated in learning new words and could learn from their classmates a lot.Â Keywords: riddle,vocabulary